An analysis of students’ nationalistic attitudes through the flag ceremony at SDN 104181 Sunggal Kanan - Asdini Indah Lestari; Yakobus Ndona; Daulat Saragi (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2025)
The weakening of nationalism among elementary students in the era of globalization highlights the need for effective character education practices in schools. Although flag ceremonies are routinely implemented, many students still perceive them as mere formalities and have not fully internalized nationalist values, indicating a gap between expected character outcomes and the reality in the field. This study aims to analyze how nationalist values are formed through flag ceremonies and positive habituation in the school environment, as well as to identify supporting and inhibiting factors in the internalization process. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving students, teachers, and school administrators. The findings show that routine practices such as flag saluting, singing the national anthem, and teacher role modeling effectively strengthen students’ discipline, responsibility, and patriotism, although challenges remain in terms of students’ varied levels of understanding and engagement. The study concludes that ceremonial school activities can serve as strategic instruments of character education when implemented consistently and supported by teacher exemplification. These results offer a contextual model that can be replicated to enhance nationalism in elementary education. Abstrak. Menguatnya arus globalisasi berdampak pada melemahnya rasa nasionalisme di kalangan siswa sekolah dasar, sehingga diperlukan pendekatan karakter yang lebih strategis dan kontekstual. Meskipun upacara bendera telah dilaksanakan secara rutin, sebagian siswa masih mengikutinya sebagai formalitas dan belum sepenuhnya memahami nilai-nilai kebangsaan, menunjukkan adanya kesenjangan antara tujuan ideal pendidikan karakter dan realitas pelaksanaannya. Penelitian ini bertujuan menganalisis proses pembentukan sikap nasionalis siswa melalui upacara bendera serta mengidentifikasi faktor pendukung dan penghambat internalisasi nilai-nilai kebangsaan di lingkungan sekolah. Pendekatan deskriptif kualitatif digunakan dengan teknik observasi, wawancara, dan dokumentasi untuk memperoleh data dari siswa, guru, dan pihak sekolah. Hasil penelitian menunjukkan bahwa pembiasaan positif melalui penghormatan bendera, menyanyikan lagu kebangsaan, dan keteladanan guru berperan langsung dalam memperkuat disiplin, tanggung jawab, dan patriotisme siswa, meskipun masih ditemukan variasi dalam pemahaman dan keterlibatan mereka. Penelitian ini menyimpulkan bahwa kegiatan seremonial sekolah dapat menjadi instrumen efektif pendidikan karakter apabila dijalankan secara konsisten dan didukung keteladanan guru. Temuan ini menawarkan model kontekstual yang dapat direplikasi untuk memperkuat nasionalisme pada jenjang pendidikan dasar.